PENERAPAN LEADER MEMBER EXCHANGE DALAM PENDIDIKAN KEJURUAN - Hartanto, Suryo (Universitas Riau Kepulauan, 2014)
This article, proposed to change a patterns and the concept of leadership in vocational education. Vocational Leadership still have a political tendency or specific social groups, the selected leader which do not possess the skill and competence of course, the problem occur are unconducive of organizations school, hampered individual career and skill, organization school is no longer running on educational track, this very inhibited development of vocational education. The proposed concept is leader member exchange theory or LMX. Basic concept of Leader Member Exchange are mutual trust, mutual respect and taking charge in developing of organization, it is considered suitable to be applied in vocational education.